ANTIULCEROGENIC ACTIVITY OF ETHANOLIC LEAF EXTRACT OF LASIANTHERA AFRICANA - Okokon, Jude E.; Antia, Bassey S.; Umoh, Emem E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The effect of ethanolic leaf extract of Lasianthera africana on experimentally induced ulcer was studied in rats. The extract (1000 – 3000mg/kg) inhibited ethanol-induced, indomethacin – induced and reserpine –induced ulcer models in a dose dependent fashion. The various degrees of inhibitions were statistically significant (p<0.01). The effect of the extract was comparable to that of the standard drugs used. Thus, Lasianthera africana extract demonstrated a good antiulcer activity which supports the antiulcer effect of this plant in traditional medicine.